PERANAN TUGAS DAN KEWENANGAN BADAN KEPEGAWAIAN NEGARA (BKN) DALAM PENGEMBANGAN KEPEGAWAIAN - Febriadi, Herry (Al Iidara Balad, 2019)
Along with the changing strategic environment and motivated by the improvement of legislation in particular in the field of personnel Duties and Authority of the State Personnel Board. The duties BKN that as the body charged with overseeing the development of staffing at this time, as for the development of these employees are divided into two, namely the development of the quality of employees and employee career development. In terms of the development of the State Civil Service Agency (BKN), the agency has the authority to regulate the displacement between functional and structural positions. In this case the State Civil Service Agency (BKN) has the task to resolve the problems concerning the development of career civil servants, particularly temporary employees. the State Civil Service Agency along with government or lemaga State involved must work together in any case related employment particularly temporary employees. This research is normative; The results showed that the State Personnel Agency must have a high commitment to employee development, both in improving the quality of employees and employee career development and the State Civil Service Agency also have to pay attention and oversee the transfer of class between the positions of structural and functional positions that should be regulated in a legislation.